RANCANG BANGUN APLIKASI BERBASIS ANDROID UNTUK PENGOLAHAN DATA PENGURUS MASJID - ADHI SUSANO (Faktor Exacta, 2016)
Public facilities such as mosque is needed in the region a tourist town one of them for worship, as for information regarding support facilities, schedule of activities which have been hard to come by, so with this research is to create a service facility information mosques integrated, up-to-date, easy and practical can be used on mobile phones that are generally based on android. So that the application is helpful to actively interact with each mosque activities. The research method used was survey data through interviews with the responsible officer then the appropriate data collection methods of observation and direct observation in the field. During the research process running the authors found it to be a potential in advancing prosperity Darussalam Mosque in Kota Wisata one of which is sustainability activity information with pilgrims, if this communication can be optimized with a variety of activities in Darussalam Mosque that it will be great potential in helping accelerate the progress of the mosque own. Finally, the authors concluded that the system has been running on this Darussalam Mosque should be developed again in the purpose of the progress and prosperity of Darussalam Mosque in Kota Wisata better. Information and communication will support the power that have developed between the pilgrims with the board Masjid Darussalam Kota Wisata.Keyword: Masjid Darussalam, Information and Android